The trouble with inventing a viscount - Lorret, Vivienne (Lorret, Vivienne. The liar's club, 2024)
"Honoria Hartley enjoys flirting far too much to consider marrying. And besides, she's been betrothed since birth to the long-lost Viscount Vandemere. But no one has actually ever met the viscount and, without an heir, the title will soon become extinct. So she's willing to do anything to keep her viscount alive, even if she has to invent him herself. Oscar Flint is a first-rate gambler. Estranged from his father's side of the family his entire life, he grew up beneath the tutelage of a legendary con artist. There isn't anyone who could pull the wool over his eyes. Not until he crosses paths with Honoria. Losing to her puts him in a bind... Until he remembers her story about a lost heir to a viscountcy. An heir that no one has ever met. Not yet, anyway. When Oscar arrives on Honoria's doorstep, claiming to be Vandemere, she is thrown for a loop. This rogue is not her viscount. The only problem is, he's quite convincing, and when he kisses her, the line between the lie and the truth becomes hazy in all the steam they create. Honoria refuses to gamble with her heart. But Oscar has never played by the rules and he's determined to win, no matter the cost"--